The LiveAbility House: A collaborative adventure in discovery learning - Kirby, Sarah D.; Sellers, Debra M. (IGI Global, 2011)
This chapter follows efforts of an online community of practice whose mission is to make individual educational experiences for family caregivers widely available. The case study illustrates the collaborative learning and creative processes of the community of practice as it worked to construct and transform informal educational content into engaging, interactive, and immersive educational tools for its intended audience. As part of its efforts, the CoP created The LiveAbility House, a virtual demonstration home, constructed in Second Life®. This virtual home is designed to teach individuals about real life universal design principles and assistive technology devices that may increase their ability to remain living at home despite physical or cognitive challenges they may encounter due to aging, illness, or disability. In addition to the creation of a virtual learning experience, the chapter also addresses plans to then take that experience out of the virtual world and apply and demonstrate learning principles in a real world setting.
Keywords: LiveAbility House; Virtual learning experience; Second Life; Virtual home; Caregivers